Protein feeds supplemented with phytase: Substitution of soybean meal by canola meal in diets for silver catfish - Rodrigues, Mariana Lins (2020)
The aim of this study was to evaluate the growth performance, intestinal histomorphometry, and body composition of juvenile silver catfish fed diets with increasing levels of inclusion (0, 25, 50, 75, and 100%) of canola meal (CM) replacing soybean meal (SM), supplemented or not with the phytase enzyme (1500 FTU kg-1). Groups of 10 fish were randomly assigned to 30 experimental units and fed their respective experimental diets for 60 days. There was a significant interaction between factors for weight gain (WG), feed conversion rate (FCR), and protein efficiency rate (PER). For WG, the highest results were evidenced in silver catfish fed diets containing 100% CM, without phytase, and 75% CM, with phytase. In FCR, better results were seen in fish fed 50, 75, and 100% CM inclusion, regardless of enzyme supplementation. PER was higher in fish fed 50% CM, without phytase. There was influence of the substitution of SM for CM for the specific growth rate (SGR), height of intestinal folds, and body mineral matter (MM). The highest SGR was observed in fish fed with 100% substitution. The greatest height of intestinal folds was observed in fish fed 75% of CM in the diet, and the highest MM was found in fish fed diets without the inclusion of CM. Canola meal can replace soybean meal in diets for juvenile silver catfish, however, we suggest new studies to understand the combined use of phytase and canola meal in diets for this species.